Antiepileptic properties of l-arginine on the models of simple and complex partial seizures = Антиэпилептические эффекты l-аргинина в условиях экспериментальных моделей простых и комплексных парциальных судорог - Polyasny, V. A. (Journal of Education, Health and Sport, 2015)
Polyasny V A. Antiepileptic properties of l-arginine on the models of simple and complex partial seizures = Антиэпилептические эффекты l-аргинина в условиях экспериментальных моделей простых и комплексных парциальных судорог. Journal of Education, Health and Sport. 2015;5(5):355-362. ISSN 2391-8306. DOI 10.5281/zenodo.17882 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A355-362 https://pbn.nauka.gov.pl/works/561486 http://dx.doi.org/10.5281/zenodo.17882 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 20.05.2015. UDK 615.213.015.2 ANTIEPILEPTIC PROPERTIES OF L-ARGININE ON THE MODELS OF SIMPLE AND COMPLEX PARTIAL SEIZURES АНТИЭПИЛЕПТИЧЕСКИЕ ЭФФЕКТЫ L-АРГИНИНА В УСЛОВИЯХ ЭКСПЕРИМЕНТАЛЬНЫХ МОДЕЛЕЙ ПРОСТЫХ И КОМПЛЕКСНЫХ ПАРЦИАЛЬНЫХ СУДОРОГ V A Polyasny В. А. Полясный Odessa National Medical University, Odessa, Ukraine Одесский национальный медицинский университет, Одесса, Украина Summary. On the model of amygdalar kindling in rats (complex partial seizures) it was shown that L-arginine (500,0 mg/kg, i.p.) caused the suppression of behavioral seizures. The effect was similar to that one induced via diphenylhydantoin (DPhG, 100 mg/kg, i.p.) administration. On the model of simple partial seizures induced in the brain cortex via penicillin solution application L-arginine (500,0 mg/kg, i.p.) elicited more pronounced decreasing of spike frequency in comparison with phenobarbital (10,0 mg/kg, i.p.), while DPhG (100 mg/kg, i.p.) did not affect focal epileptogenesis. It is concluded that L-arginine possessed efficacy both against simple and complex partial seizures. Key words: L-arginine, kindling, epileptic focus, penicillin, diphenylhydantoin, phenobarbital. Резюме. На модели киндлинга миндалины у крыс (комплексная парциальная эпилепсия) показано подавление поведенческих судорог под влиянием L-аргинина (500,0 мг/кг, в/бр). Выраженность эффекта была подобна таковой, наблюдавшейся после применения дифенилгидантоина (ДФГ, 100 мг/кг, в/бp.). На модели простых парциальных судорог, индуцированных в коре головного мозга аппликацией раствора пенициллина, L-аргинин (500,0 мг/кг, в/бр) способствовал более выраженному снижению частоты разрядов, чем фенобарбитал (10,0 мг/кг, в/бp), в то время как ДФГ (100 мг/кг, в/бp) не влиял на фокальный эпилептогенез. Сделан вывод, что L-аргинин является эффективным в отношении простых и комплексных парциальных судорог. Ключевые слова: L-аргинин, киндлинг, эпилептический очаг, пенициллин, дифенилгидантоин, фенобарбитал. ПРОТИЕПІЛЕПТИЧНІ ЕФЕКТИ L-АРГІНІНА ЗА УМОВ ЕКСПЕРИМЕНТАЛЬНИХ МОДЕЛЕЙ ПРОСТИХ ТА КОМПЛЕКСНИХ ПАРЦІАЛЬНИХ СУДОМ. На моделі кіндлінгу мигдалику у щурів (комплексна парціальна епілепсія) показано пригнічення поведінкових судом під впливом L-аргініну (500,0 мг/кг, в/очер). Цей ефект за виразністю був подібним до такого, який спостерігався після застосування дифенілгідантоїну (ДФГ, 100 мг/кг, в/очеp). На моделі простих парціальних судом, які індукували в корі мозку шляхом аплікації бензилпеніциліну натрію, L-аргінін (500,0 мг/кг, в/очер) спричиняв більш виразне зниження частоти спайкових потенціалів порівняно з таким ефектом фенобарбіталу (10,0 мг/кг, в/очеp), в той час як ДФГ (100 мг/кг, в/очеp.) не впливав на осередковий епілептогенез. Зроблено висновок, що L-аргінін є ефективним у відношенні щодо простих та комплексних парціальних судом. Ключові слова: L-аргінін, кіндлінг, епілептичний осередок, пеніцилін, діфенілгідантоїн, фенобарбітал.